PENGARUH INVESTASI, BELANJA MODAL, DAN TENAGA KERJA TERHADAP PDRB KABUPATEN/KOTA DI PROVINSI BALI - Suryantari, A. A. Ayu Chandra; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Inter-regional income disparities is a common aspect of economy activities in a region.  Gross Regional Domestic Product (GRDP) is an indicator that can describe the level of economic growth of a region. This study aims to determine and analyze the effect of investment, capital expenditure, and labor simultaneously and partially on the GRDP of districts / cities in Bali province, as well as to find out and analyze the variables between investment, capital expenditure and labor which have the most dominant influence on regency GRDP. / city in the province of Bali. The data used in this research is time series data for the period 2014-2018 and covers nine districts / cities in Bali Province. The technique used multiple linear regression. Based on the results, it shows that investment, capital expenditure and labor have a significant effect simultaneously on the GRDP of regencies / cities in Bali province and investment, capital expenditure and labor have a positive and partially significant effect on the GRDP of districts / cities in Bali Province. And in this study, investment has the most dominant influence on the GRDP of districts / cities in Bali Province. Keywords: investment, capital expenditure, gross regional domestic product